Sanear, prever e embelezar : o engenheiro Saturnino de Brito, o urbanismo sanitarista e o novo projeto urbano do PRR para o Rio Grande do Sul (1908-1929) - Lopes, André Luís Borges (2013)
The objective of this study is to describe the set of works made by engineer Francisco Rodrigues Saturnino de Brito and his ideas of urban sanitation, served as guidance to the formation of a new urban project in Rio Grande do Sul. Requested in the context of establishment of the Republic these works emerge as a political tool of the Republican Party-Rio Grande (PRR) and its new urban design, thus guiding the progress that was required with the installation of the new regime. These works should be thought also as an instrument of intervention in urban space, based on technical studies prepared by an expert quite attuned to the knowledge of his time